2022
DOI: 10.3390/biology11030347
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in O-GlcNAcylation Mitigates the Severity of Inflammatory Response in Cerulein-Induced Acute Pancreatitis in a Mouse Model

Abstract: Acute pancreatitis (AP) involves premature trypsinogen activation, which mediates a cascade of pro-inflammatory signaling that causes early stages of pancreatic injury. Activation of the transcription factor κB (NF-κB) and secretion of pro-inflammatory mediators are major events in AP. O-GlcNAc transferase (OGT), a stress-sensitive enzyme, was recently implicated to regulate NF-κB activation and inflammation in AP in vitro. This study aims to determine whether a pancreas-specific transgenic reduction in OGT in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
(75 reference statements)
0
1
0
Order By: Relevance
“…The results showed that EF-treatment suppressed the expression of IL-1β, IL-6, TNF-α, iNOS and COX-2 both at mRNA and protein levels, and reduced the concentration of NO in the cell supernatant induced by LPS in a dose-dependent manner ( Figure 2A–L ). Neuclear factor kappa-B (NF-κB), a canonical regulator of inflammation and immunity, is activated by inflammatory stimuli and translocated into the nucleus to trigger the transcription of downstream proinflammatory genes, involving in various cellular functions ( Guo et al, 2022 ; Moore et al, 2022 ). As shown in Figures 2M,N , EF-treatment could reduce the ratio of phosphorylated-NF-κB p65/p65, phosphorylated-IκBα/IκBα and interfere the translocation of NF-κB p65 from cytoplasm to nucleus in LPS-stimulated primary microglia.…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that EF-treatment suppressed the expression of IL-1β, IL-6, TNF-α, iNOS and COX-2 both at mRNA and protein levels, and reduced the concentration of NO in the cell supernatant induced by LPS in a dose-dependent manner ( Figure 2A–L ). Neuclear factor kappa-B (NF-κB), a canonical regulator of inflammation and immunity, is activated by inflammatory stimuli and translocated into the nucleus to trigger the transcription of downstream proinflammatory genes, involving in various cellular functions ( Guo et al, 2022 ; Moore et al, 2022 ). As shown in Figures 2M,N , EF-treatment could reduce the ratio of phosphorylated-NF-κB p65/p65, phosphorylated-IκBα/IκBα and interfere the translocation of NF-κB p65 from cytoplasm to nucleus in LPS-stimulated primary microglia.…”
Section: Resultsmentioning
confidence: 99%